Investors Reaction to Bad News of COVID 19 (Evidence for Food and Beverage stocks: Comparison between IDX and BIST) - Idah Zuhroh; Della Andrieanny Putri (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2021)
The study aims to examine the reaction of stock investors in the food and beverage sub-sector to the announcement of COVID-19 on the Indonesia Stock Exchange (IDX) and the Turkish Istanbul Exchange (BIST). The approach method is an Event Study by comparing the return and volume of trading activity before and after the announcement of COVID-19 on the Indonesian and Turkish Stock Exchanges. The research sample is 32 IDX stocks and 27 BIST stocks. Observation period 13 weeks before and after the announcement. The distribution of the data is the basis for the selection of hypothesis testing. The study results showed that IDX investors reacted positively to the announcement of the COVID-19 pandemic, where stock returns were higher than before. Likewise, VTA was higher after the information, although not significant. Meanwhile, on the Turkish Stock Exchange, investors' positive reactions were shown by stock returns and trading volume activity, which was significantly higher after the COVID-19 announcement than IDX, which tends to stagnate.